Alkaloid Production in Tissue Cultures of Papaver somniferum L. cv. Office-95 - Oluk, Esin Akçam (Plant Tissue Culture and Biotechnology, 2008)
The capacity of alkaloid synthesis was examined in embryogenic callus tissues of Turkish opium poppy, Papaver somniferum L cv. office-95. Eight months old cultures grown in hormone-free MS were examined for alkaloid content. They were found to produce codeine at a level of 1.2 x 10-2, the baine 2.5 x 10-3, noscapine 2.2 x 10-3, morphine 1.6 x 10-3 and papaverine 5.2 x 10-4 % FW. Key words: Papaver somniferum, Embryogenic callus, Alkaloids DOI = 10.3329/ptcb.v16i1.1098 Plant Tissue Cult. & Biotech. 16(1): 1-4, 2006 (June)